Blood winter - Francis, Diana Pharaoh (Horngate witches book ;, 2012)
Max always does her job, no matter how brutal and bloody. That?s how it?s been ever since she was enslaved by a witch, turned into a supernatural warrior, and assigned to protect the coven of Horngate. But her job just got harder. . . . Waves of wild magic have returned much of the world to a time when fairy tales were real and danger now lurks behind every tree and bush. As winter descends and food, heat, and water are harder to come by, many have turned to Benjamin Sterling for protection. Leader of the Earth?s Last Stand cult, Sterling claims to be the Hand of God, but his power and charisma secretly come from a dark and terrible source. With devout followers eager to do his sadistic bidding, he has his eyes on Horngate and its magical inhabitants. To save those she loves, Max will knowingly walk into a trap. But when the cult strips Max?s soul bare for all to see, will even Alexander?her lover and her strength?remain? And if she were to lose him, what does it matter if she gains the whole world. . . .